Examine the Growing Problem of Antibiotic Resistance and its impact on Public Health (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Antibiotic resistance has been rising rapidly in recent years, with Saudi Arabia having thehighest frequency of resistant infections in the Gulf Region. Despite legal restrictions on antibioticdistribution, their misuse remains widespread. The purpose of this research was to examine how muchSaudi university students know about antibiotic resistance and how often they properly utilize antibiotics.The research method was a cross-sectional analytic approach. Bachelor students' perspectives onantibiotic resistance and antibiotic usage were gathered using a self-administered survey. To recruit thenecessary 825 individuals, a two-stage stratified cluster sampling procedure was used. Seventy-fivepercent or more of college students knew about antibiotic resistance (95 confidence interval [CI]72.09–77.98), and 54.67 percent [CI] 51.26–58.03 percent knew about antibiotic resistance as a publichealth concern. The most prevalent types of antibiotic abuse were not completing the full course oftreatment or taking medications that had expired (95 CI 63.63 - 70.04). Knowing about antibioticresistance reduced the likelihood that students would abuse antibiotics by 27.96 percent (OR = 0.7204, p= 0.0642). One's odds of misusing antibiotics drops by 51.32 percent if one is aware that antibioticresistance is a public health concern (OR = 0.4868, p 0.0001). Antibiotic abuse decreases when peopleare aware of the problem of antibiotic resistance. More effort should be put into spreading awarenessabout the dangers of antibiotic overuse and the rise of antibiotic resistance.